2013
DOI: 10.12965/jer.130003
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill exercise improves behavioral outcomes and spatial learning memory through up-regulation of reelin signaling pathway in autistic rats

Abstract: Autism is a complex neurodevelopmental disability with impairments of social interaction and communication, and repetitive behavior. Reelin is an extracellular glycoprotein that is essential for neuronal migration and brain development. Neuroprotective effects of exercise on various brain insults are well documented, however, the effects of exercise on autism in relation with reelin expression are not clarified. In the present study, we investigated the effects of treadmill exercise on the functional recovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 41 publications
(56 reference statements)
1
57
0
1
Order By: Relevance
“…In this respect, exercise activates cAMP response element-binding protein, mitogen-activated protein kinases, and synapsin, 31,32 and increases phosphorylation of AKT in the brain. 33 Muscle metabolic adaptations are more thoroughly understood. 13,17,34,35 Myocytes react to exercise-induced increases in reactive species, increasing the expression of SOD, CAT, and GPx in a mechanism that is dependent on nuclear factor κB, 17,36,37 nuclear erythroid 2 p45-related factor 2, 34 and PGC-1α.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, exercise activates cAMP response element-binding protein, mitogen-activated protein kinases, and synapsin, 31,32 and increases phosphorylation of AKT in the brain. 33 Muscle metabolic adaptations are more thoroughly understood. 13,17,34,35 Myocytes react to exercise-induced increases in reactive species, increasing the expression of SOD, CAT, and GPx in a mechanism that is dependent on nuclear factor κB, 17,36,37 nuclear erythroid 2 p45-related factor 2, 34 and PGC-1α.…”
Section: Discussionmentioning
confidence: 99%
“…Since the samples of these two researches are small, nine and five autistic subjects respectively, these conclusions need to be verified by a larger amount of samples. Similarly, in a study on valproic acid (VPA) inducing autistic symptoms in rats, researchers found that the expression of PI3K and p‐AKT in the hippocampus of the autistic rats was decreased, and the number of caspase‐3 positive cells was increased (Seo et al, 2013). Moreover, the researchers found that in the cerebellum of the autistic rat pups, the expression of Bcl‐2 was decreased, whereas Bax was increased (Kim et al, 2013).…”
Section: Igf‐i/pi3k/akt/mtor Is Associated With Autism Spectrum Disormentioning
confidence: 99%
“…Structural connectivity at the neuron level is, to date, actually measured directly only postmortem, and is principally achieved with antero- or retrograde tracers in experimental animals. 10,11 The advent of water-diffusion sensitivity in MRI (most commonly practiced as diffusion tensor imaging [DTI]) provides a macroscopic view of the ultrastructural organization of the tissue within the imaged voxel. Within the white matter of the brain, where axon trajectories are the principal cellular organizational construct, water diffusion tends to reflect the average magnitude of diffusion, or mean diffusivity (which is related to the presence of impediments to diffusion such as density of cellular components or fluidity of the intracellular medium), and the average orientation of the cellular components, as water tends to diffuse in parallel to, as opposed to against, the impediments within the cell.…”
Section: Introductionmentioning
confidence: 99%